Does analysis brevity result in loss of control? A consecutive case series of 26 single‐session interview‐informed synthesized contingency analyses. (31st October 2019) - Jessel, Joshua; Metras, Rachel; Hanley, Gregory P.; Jessel, Catherine; Ingvarsson, Einar T.
Abstract : A believable demonstration of control over problem behavior is a necessary component of the functional analysis process. Control during a functional analysis has traditionally been defined in a binary manner: Differentiated outcomes point to an identifiable function and undifferentiated outcomes do not. However, it might be beneficial to characterize control as strong, moderate, or weak in order to evaluate the strength of evidence for experimental control during an efficient functional analysis format that requires only a single session. We analyzed the levels of control using 26 single‐session interview‐informed synthesized contingency analyses (IISCAs). Although shorter session duration (i.e., first 3 or 5 min of each session) tended to reduce the level of control, the majority of single‐session IISCAs resulted in evidence indicating strong levels of control when data from the full 10‐min session were included in the analysis.